Diversity of Mammalian Fauna and Conservation Issues of Dhankuta Municipality of Dhankuta District, Nepal - Subba, Suren (Rupantaran: A Multidisciplinary Journal, 2023)
Dhankuta municipality is a mid-hill town in Dhankuta district, Province 1, Nepal. The municipality consists of 10 wards scattered across 111.6 square kilometers of geographical area and is situated between 26°59’59’’ and 27°02’55’’ north latitude and 87°17’52’’ and 87°23’09’’ east longitudes. Mammalian diversity in the municipality has not been so far recorded. The present study was conducted from August 2021 to July 2022 with a view to bridging this knowledge deficit and presenting an up-to-date account of the mammalian species in the agricultural fields and forests of the municipality based on questionnaire survey, direct sightings and indirect evidence. A total of 19 mammal species belonging to 7 orders and 13 families were registered. Among 19 species, 6 species belonged to Carnivora, 2 species to Cetartiodactyla, 3 species of Primate, 5 species to Rodentia and 1 each to Chiroptera, Eulipotypha, Lagomorpha. The major threats to mammalian fauna of the municipality include habitat loss and degradation, persecution, human-wildlife conflict and poaching. For long-term conservation of wild mammals more research is needed on their population genetics, habitat ecology, food web and climate change vulnerability. The information contained in the present study is expected to form the baseline for further development and research in the field of mammalian conservation in the municipality.